2009
DOI: 10.1111/j.1365-2613.2009.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

PDEs1‐5 activity and expression in tissues of cirrhotic rats reveal a role for aortic PDE3 in NO desensitization

Abstract: Liver cirrhosis is associated with increased nitric oxide (NO) production in the vasculature. We have previously demonstrated that aorta from rats with liver cirrhosis have a reduced relaxant response to NO donors that is corrected by DMPPO, a PDE5-specific inhibitor. Vasodilator responses to DMPPO itself were also reduced in rings from cirrhotic rats. These results supported previous suggestions that upregulation of PDE5 in liver cirrhosis might contribute to renal sodium retention, and consequently modulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
3
6
0
Order By: Relevance
“…Moreover, cAMP plays a major role in metabolism and homeostasis regulation, being involved in heart failure pathophysiology . Cortical cAMP‐PDE activity was higher than cGMP‐PDE activity in all groups, as previously demonstrated . cAMP‐PDE activity was attributable mainly to PDE4 and PDE2 activities, which is in agreement with previous results showing that PDE4 activity is high in rats cortical tubules and PDE2 in glomeruli .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, cAMP plays a major role in metabolism and homeostasis regulation, being involved in heart failure pathophysiology . Cortical cAMP‐PDE activity was higher than cGMP‐PDE activity in all groups, as previously demonstrated . cAMP‐PDE activity was attributable mainly to PDE4 and PDE2 activities, which is in agreement with previous results showing that PDE4 activity is high in rats cortical tubules and PDE2 in glomeruli .…”
Section: Discussionsupporting
confidence: 92%
“…In sham, MI, and MI‐PER rats, PDE2 and PDE1, but not PDE5, accounted for most of cGMP‐PDE cortical activity. In previous studies , the contribution of PDE1 was strong as in the present study, although PDE5 also played an important role in cGMP hydrolysis . This strong contribution of PDE1 could account for the interesting antihypertensive activity of a novel sulfonamide compound which has been described, acting as a PDE1 inhibitor .…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Such increased enzyme activity rapidly catabolizes the second messenger cGMP (Lee and Humphreys, 1996). In addition, Tahseldar-Roumieh et al (2009) found that, PDE3 activity increased in CBDL rats and it may play a role in the decreased vascular responsiveness to nitroglycrine an Table 1 Scores for degeneration, necrosis, inflammation, fibrosis and number of biliary ducts in sham control rat treated with vehicle; CBDL treated with vehicle; CBDL treated with cilostazol (9 mg/kg/day, by gavage). These parameters were determined by the end of the 1st and 3rd week after CBDL.…”
Section: Discussionmentioning
confidence: 99%